2018
DOI: 10.1590/0034-7167-2017-0239
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene: nurses’ adherence after training

Abstract: After training, nurses' adherence to hand hygiene improved, particularly when compared to the other professionals involved. Despite its simplicity, the implementation of a training program and its subsequent follow-up have a positive on nurses' attitudes and adherence to hand hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 6 publications
(32 reference statements)
1
17
0
4
Order By: Relevance
“…Chart 1 shows the search mechanism used in each database and the number of articles retrieved. Publications excluded because they are unavailable and/or are not original articles and/or do not answer the guiding question (n=8,835) 9,109 publications were found and 25 articles were eligible in order to compose the sample of the present study ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chart 1 shows the search mechanism used in each database and the number of articles retrieved. Publications excluded because they are unavailable and/or are not original articles and/or do not answer the guiding question (n=8,835) 9,109 publications were found and 25 articles were eligible in order to compose the sample of the present study ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has demonstrated the importance of promoting adequate HH technique compliance among health professionals in order to reduce the high rates of infections caused by multidrug resistant microorganisms (4)(5)(6)(7)(8)(9) . However, low compliance with these practices remains a challenge for practitioners and health institutions, especially in developing countries, which may present an HCAI rate up to 20 times higher than in developed countries (10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the challenges faced in the health area, measures oriented toward preventing and controlling infections stand out. The consequences of healthcare-associated infections (HAIs) can be seen in morbimortality rates and the increase in healthcare-related costs (1)(2) .…”
Section: Introductionmentioning
confidence: 99%
“…Although careful hand hygiene is the most effective measure to prevent infections (2,(5)(6) , adherence to this practice remains low even in environments where resources and conditions are available (5)(6)(7)(8)(9) . Additionally, few interventions are considered long-lasting (7) .…”
Section: Introductionmentioning
confidence: 99%